Vulcan petawatt: Design, operation and interactions at 5 × 10 20Wcm-2 - Danson, C; Brummitt, P; Clarke, R; Collier, J; Fell, B; Frackiewicz, A; Hawkes, S; Hernandez-Gomez, C; Holligan, P; Hutchinson, M; Kidd, A; Lester, W; et al. (2005)

(untitled)
The Vulcan Nd:glass laser at the Central Laser Facility (CLF) is a petawatt (1015 Watts) interaction facility, designed to deliver irradiance on target of 1021W.cm-2 for the UK and international user community. The facility came online to users in 2002 and considerable experience has been gained operating Vulcan in this mode. The facility delivers a wide-ranging experimental program in fundamental physics and advanced applications. This includes the interaction of ultrahigh intensity light with matter, fast ignition fusion research, photon induced nuclear reactions, electron and ion acceleration by light waves, and the exploration of the exotic world of plasma physics dominated by relativity. We report on the first year's operation of the facility and the highlights of the experimental campaigns. Copyright © 2005 Cambridae University Press.